Anthropometric Assessment of Patients on Maintenance Hemodialysis at a Tertiary Care Hospital in Nepal - Agrawaal, Krishna Kumar (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Protein energy wasting is common in hemodialysis patients and is linked to increased morbidity and mortality. Anthropometric measurements such as skin fold thickness, mid arm circumference and mid arm muscle circumference are widely used to assess nutritional status in patients on maintenance hemodialysis. Subjective global assessment dialysis malnutrition score is used to classify patients’ nutritional status. The aim of this study was to assess the nutritional status using anthropometry. MATERIAL AND METHODS This descriptive cross-sectional study was carried out from 1st October 2021 till 30th September 2022 under Nephrology unit, Department of Internal Medicine at Universal college of Medical Sciences, Bhairahawa, Nepal. Ethical clearance was taken. Subjective Global Assessment Dialysis Malnutrition score was calculated. Triceps skin fold thickness, Mid arm circumference and Mid arm muscle circumference was measured. Convenience sampling was used. The data were analyzed using the Statisti- cal Package for the Social Science version 17. RESULTS In this study of 50 patients undergoing MHD for at least 3 months, the Mean age of population was 42.00 ±15.26 years. Nearly half of the study population 21 (42%) was having mild to moderate malnutrition using subjective global assessment dialysis malnutrition score and none had severe malnutrition. CONCLUSION There is mild to moderate malnutrition in patients on maintenance hemodialysis at our center based on anthropometric measure- ment including subjective global assessment dialysis malnutrition score tool.